Employee Performance: Compensation, Motivation and Work Environment with Job Satisfaction as an Intervening Variable at Tiumang District Community Health Center - Revina Marlin; Yulasmi Yulasmi; Zefriyenni Zefriyenni (International Journal of Economics and Management Research, 2025)
The Tiumang Community Health Center is a public health facility located in Dharmasraya Regency, West Sumatra. This health center provides various health services to the community, including general medical services and maternal and child health services. With a staff of 71 people, the Tiumang Health Center plays a crucial role in improving the health status of the community in the region.The research method used is a quantitative approach with an associative design. The research sample consists of 71 employees taken through a saturated sampling technique. Data were collected using a questionnaire consisting of questions regarding the variables being studied. Data analysis was performed using Partial Least Squares (PLS) with SmartPLS.The results of the study indicate that compensation has a significant positive effect on job satisfaction, where the T-statistic value reaches 6.436 (p < 0.05). Work motivation also has a significant positive effect on job satisfaction with a T- statistic of 5.848 (p < 0.05). However, the work environment does not have a significant effect on job satisfaction (T-statistic 1.530, p > 0.05).On the other hand, compensation and work motivation significantly positively affect employee performance, with T-statistic values of 2.988 and 2.579, respectively (p < 0.05). The work environment shows a positive but not significant effect on employee performance (T-statistic 1.802, p > 0.05). Job satisfaction is proven to mediate the effect of motivation on employee performance, but it does not mediate the effect of compensation and the work environment.This research provides important contributions to human resource management at the Tiumang Community Health Center, with recommendations to improve compensation and work motivation to enhance employee satisfaction and performance.